2021
DOI: 10.1186/s12888-021-03631-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of metabolic syndrome among patients with schizophrenia in Ethiopia

Abstract: Background Globally, the prevalence of metabolic syndrome (MetS) is higher among patients with schizophrenia than the general population, and this leads to higher morbidity and mortality in this population. The aim of this study was to investigate the MetS prevalence among patients with schizophrenia in Ethiopia. Methods We conducted a cross-sectional analysis of baseline data of 200 patients with schizophrenia recruited from Amanuel Mental Special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…A previous meta-analysis found that the overall rate of metabolic syndrome in patients with schizophrenia was 32.5%, with only minor differences across countries and treatment settings, and no differences between genders [ 60 ]. Similar findings were recently reported on Chinese patients with schizophrenia [ 61 ], as well as on patients with schizophrenia in developing countries [ 62 ], although data are limited at present. Contributing factors to obesity are the side effects of antipsychotic medication, such as weight gain, metabolic abnormalities and sedation.…”
Section: Contributing Factors To Increased Mortalitysupporting
confidence: 89%
“…A previous meta-analysis found that the overall rate of metabolic syndrome in patients with schizophrenia was 32.5%, with only minor differences across countries and treatment settings, and no differences between genders [ 60 ]. Similar findings were recently reported on Chinese patients with schizophrenia [ 61 ], as well as on patients with schizophrenia in developing countries [ 62 ], although data are limited at present. Contributing factors to obesity are the side effects of antipsychotic medication, such as weight gain, metabolic abnormalities and sedation.…”
Section: Contributing Factors To Increased Mortalitysupporting
confidence: 89%
“…MetS is defined by combination of abdominal obesity, high blood pressure, low high-density lipoprotein cholesterol, elevated triglycerides, and hyperglycemia (24). MetS was long considered to be a comorbid outcome of schizophrenia after years of medication even in young patients, associating with the increasing risk for SCD and CVD mortality among schizophrenia (25,26). Clinical studies suggested that the incidence of hepatic steatosis may serve as a predictor of CVD both in the general population and in patients with schizophrenia (27).…”
Section: Discussionmentioning
confidence: 99%